Reframing bi-nationalism in Palestine-Israel as a process of settler decolonisation - Todorova, Teodora (Wiley, 2015)
This paper examines some of the emerging critical civil society debates in relation to the one-state solution being the most appropriate geo-political arrangement for the articulation of freedom, justice and equality in Palestine-Israel. This is done with reference to the Israeli Committee Against House Demolitions’ 2012 statement in support of a bi-national state and the ensuing critiques it attracted from Palestinian supporters of the one-state position. Drawing on these debates which have largely revolved around Jewish Israeli rights to political self-determination in Palestine-Israel, this paper proposes that alternative versions of self-determination as cultural rights for the established Hebrew-speaking national community represent a more inclusive form of self-determination in the eventuality of decolonisation.